Delayed Postpartum Eclampsia - Kholoud A. Ghamri (Journal of King Abdulaziz University: Medical Sciences, 2023)
Eclampsia is an important cause of maternal mortality in the developing world. While eclampsia typically occurs before or within two days of delivery, it can still occur between two days and a month after the patient delivers, known as delayed postpartum eclampsia. The presented case is a good example of late postpartum eclampsia, and it highlights the importance of prompt recognition and diagnosis during the postpartum period in order to initiate the appropriate treatment.